2021
DOI: 10.1016/j.heliyon.2021.e06505
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural differences in foreign language learning strategy preferences among Hungarian, Chinese and Mongolian University students

Abstract: The present study explores English as a foreign language (EFL) learning strategies used in Hungarian, Chinese, and Mongolian university students with different cultural and linguistic backgrounds. A total of 519 university students participated in the survey from the three different countries. The Strategy Inventory for Language Learning (SILL), developed by Rebecca Oxford (2003), was administered to explore cross-cultural differences in strategy use in the study. To explain cultural divergences, we employed H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 23 publications
(33 reference statements)
1
12
0
1
Order By: Relevance
“…One major area for researchers has been to find out what set of strategies foreign language learners rely on the most (Platsidou and Sipitanou, 2015;Alhaysony, 2017;Charoento, 2017;Dawadi, 2017;Habók and Magyar, 2018a,b, 2019, 2020Habók et al, 2021). Overall, results have concluded moderate use of LLS among participants.…”
Section: Research On Language Learning Strategiesmentioning
confidence: 94%
See 1 more Smart Citation
“…One major area for researchers has been to find out what set of strategies foreign language learners rely on the most (Platsidou and Sipitanou, 2015;Alhaysony, 2017;Charoento, 2017;Dawadi, 2017;Habók and Magyar, 2018a,b, 2019, 2020Habók et al, 2021). Overall, results have concluded moderate use of LLS among participants.…”
Section: Research On Language Learning Strategiesmentioning
confidence: 94%
“…The most frequently used strategies are cognitive, metacognitive, and compensation strategies, while affective and memory strategies are the least preferred. Habók et al (2021) have pointed out the different strategy preferences in different cultural contexts. Their results reinforced the preferred use of metacognitive strategies in both European and Asian contexts.…”
Section: Research On Language Learning Strategiesmentioning
confidence: 99%
“…In the EFL context before learners are trained to manage and monitor their reading activities, they may, in fact, first and foremost need help with the development of the positive affect towards the reading task. Habók et al (2021) cautioned strategy-based EFL reading instruction may not be a one-size-fits-all approach; students in different EFL contexts had different LLS priorities. The revealed cultural patterns of Thai EFL readers' LLS priorities for the learning-to-read and for the test-taking purposes implicated an effective strategy-based reading instruction needs to consider culturally sensitive strategic dimensions relevant to diverse contexts of EFL learners in different countries.…”
Section: Discussionmentioning
confidence: 99%
“…Anderson (2005, p. 763), however, cautioned various factors, including learners' cultural backgrounds, age, educational background, life experience, affective factors, and the learners' and teachers' beliefs about language learning, should be considered when strategy instruction is undertaken. Regarding learners' cultural backgrounds, Habók et al (2021) reported that while Hungarians preferred cognitive strategies, Mongolian and Chinese students preferred affective strategies. The present study of learning-to-read and reading test-taking strategies in the EFL context of Thailand, therefore, can help add an additional light on cultural patterns of strategy priority.…”
Section: Reading Strategy-based Instructionmentioning
confidence: 99%
“…Thus, authentic materials which are taken from the real communication of the English native speakers are highly recommended to be used during the teaching and learning process [43]. Then, it moves to cross-cultural understanding, which means both the student's culture and the target language should be introduced to build cultural awareness [44], [45]. Cross-cultural understanding in the EFL context is crucial for the learners to help them become intercultural beings [46], [47].…”
Section: Language and Culture In Efl Contextmentioning
confidence: 99%